PENGHAMBATAN AKTIVITAS XANTHINE OXIDASE OLEH EKSTRAK ETANOL AKAR SAMBILOTO (Andrographis paniculata, Ness) SECARA IN VITRO - Ulfah Septianingsih; Hari Susanti; Wahyu Widyaningsih (Universitas Ahmad Dahlan, 2012)
Sambiloto root of which contained of flavonoids used by the people fortraditional medicine. In the previous publication, an effective xanthine oxidaseinhibitory activity of flavonoids was reported. In research, in vitro xanthine oxidaseinhibitory activity of etanolic root extract of Andrographis paniculata was determinedand Allopurinol was used as a control. The etanolic extract was succesively extractedin a Soxhlet with petroleum eter. Inhibition of xanthine oxidase by etanolic extract wasmeasured the decrease of uric acid production and monitored by spectrophotometer at295 nm with xanthine as substrat. The enzyme inhibitory activity was calculated, andthen IC50 was determined. The result of analyzed with Kruskal Wallis and MannWhitney at 95% confidental level . The flavonoids of etanolic extract were separated onusing by paper chromatography and the spot changing was determined using UV 366with and without amonia.The result of the research showed that the etanolic extract ofAndrographis paniculata inhibited xanthine oxidase activity with IC50 16,54 Âµg/mlwhile Allopurinol 4,29 Âµg/ml. The etanolic extract contained flavon or flavonol.